2011
DOI: 10.4049/jimmunol.1002218
|View full text |Cite
|
Sign up to set email alerts
|

Dicer Insufficiency and MicroRNA-155 Overexpression in Lupus Regulatory T Cells: An Apparent Paradox in the Setting of an Inflammatory Milieu

Abstract: Systemic lupus erythematosus is a chronic autoimmune disease characterized by loss of tolerance to self-Ags and activation of autoreactive T cells. Regulatory T (Treg) cells play a critical role in controlling the activation of autoreactive T cells. In this study, we investigated mechanisms of potential Treg cell defects in systemic lupus erythematosus using MRL-Faslpr/lpr (MRL/lpr) and MRL-Fas+/+ mouse models. We found a significant increase in CD4+CD25+Foxp3+ Treg cells, albeit with an altered phenotype (CD6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
102
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 36 publications
4
102
0
Order By: Relevance
“…Here, they found that 12 miRNAs increased and 54 reduced in Treg cells from diseased patients compared with healthy donor controls. 149 Our recent miRNA microarray studies have also identified similar patterns of miRNA expression in a Treg cell line as the studies above (unpublished data). These investigations bring a correlative expression of miRNA in diseased conditions, but whether or not miRNA profile changes arise as a contributor or as a consequence of inflammation require further investigation.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…Here, they found that 12 miRNAs increased and 54 reduced in Treg cells from diseased patients compared with healthy donor controls. 149 Our recent miRNA microarray studies have also identified similar patterns of miRNA expression in a Treg cell line as the studies above (unpublished data). These investigations bring a correlative expression of miRNA in diseased conditions, but whether or not miRNA profile changes arise as a contributor or as a consequence of inflammation require further investigation.…”
supporting
confidence: 48%
“…147 During diabetes, an increased miR-510 and decreased miR-342 and miR-191 expressions were found in Treg cells of diseased patients compared with healthy controls. 148 In a mouse model of systemic lupus erythematosus, Divekar et al 149 had an unexpected observation of a decrease in Dicer but an increase in miR-155 expression in Treg cells from diseased mice prone to systemic lupus erythematosus, which suggests the existence of a Dicer-independent miR-155 processing mechanism that precedes the onset of disease. Here, they found that 12 miRNAs increased and 54 reduced in Treg cells from diseased patients compared with healthy donor controls.…”
mentioning
confidence: 99%
“…60 Furthermore, T REG cell suppressive functions are reduced in SLE patients and MRL mice, and it is thought that this is due to elevated levels of IL-6, which inhibits T REG cell function. 42,94,95 T REG cells have significantly higher expression of HSP90 than T cells. The high expression of HSP90 in T REG suggests a role for HSP90 in FoxP3 expression and may explain why we found higher levels of FoxP3 2 CD3 1 CD8 1 T cells.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 89%
“…36,[38][39][40][41] Splenocyte populations are often altered in autoimmune mice including differences in T-cell subtypes (including T regulatory cells (T REG )) and also alterations in B-cell subtypes. 36,37,42,43 HSP90 has been implicated in studies investigating similar autoimmune diseases and it has been reported that T cells respond to extracellular HSP90 by increasing their anti-inflammatory cytokines. 44 Other recent work has shown that T-cell activation by the T-cell receptor is dependent on functioning HSP90.…”
Section: Introductionmentioning
confidence: 99%
“…This results in impaired immunosuppression capacity, DC apoptosis, and increased inflammatory cytokine and chemokine production (Tili et al, 2007;Lu et al, 2011;Tili et al, 2011;Trotta et al, 2012). Previous studies have reported the presence of high amounts of miR-155 in various types of cancer, as well as in autoimmune diseases such as SLE (Divekar et al, 2011), but not in psoriasis.…”
Section: Discussionmentioning
confidence: 99%